Homens em movimento: pesquisa qualitativa da masculinidade na geração X e na geração Y - Angelico, Sonia Ligia (2025)
The scope of this work is to identify how generation X (born between 1965 and 1979) and generation Y (born between 1980 and 1994) cisgender heterosexual men, in their private space, are managing to work out their emotional issues at home, with their partner, as fathers and in their daily lives, in face of all the generational changes that are taking place in the digital world, in society, at work, in the family and in relationships. In order to understand this, we will bring in knowledge that broadens our view, based on concepts about masculinities, gender, sexuality, fatherhood and generational changes. Our aim is to find out whether there are demands and suffering in the private world belonging to the generations, and to understand whether there have been generational gender differences in male behavior between them (generations). As this is a qualitative study, the research was carried out with two focus groups, with participants from each generation separately. The meeting was recorded and then the recordings were transcribed. Once the data had been collected, it was sent to a professional textual analysis software called IRaMuTeQ, or Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires. Once the researcher had all the textual analysis material obtained by IRaMuTeQ in hand, she analyzed its content to find repetitive patterns of TS meanings (text segments), to understand the classification and search for themes. The theme was then placed next to each sentence brought in by the participants who were already in their classes. After defining and naming the themes in each class, it was possible to finalize and produce the writing. As for the results obtained in the research, we can say that there have been and are being many generational changes. It was found that generation X brings paternity as a relationship and the role of the generous father; insecurity in educating; resistance to female autonomy; earning money and a career; adapting to new family realities in terms of domestic roles. Continuing with generation Y on the subject, there is an expectation to be a different man, and 41.2% of the participants responded that they see homosexuality as a threat to male identity; the value of men as professional success; the pressure to adapt to social norms without losing their gender identity. They also commented on their conflict and suffering in having to correspond to hegemonic masculinity with the economic crisis we are experiencing; having to deal with the demands of friends and society in relation to sexual performance; seeing their mother as a non-model (authoritarian and controlling); changes in their father's image (identity and belonging) and empathy with their father's suffering. Another important point is the need for a social agreement uniting older generations with younger ones, whether in the family, at work, with friends or in companies, so that there can be exchanges and dialogues to build healthier interactions